2006
DOI: 10.1093/humrep/dei466
|View full text |Cite
|
Sign up to set email alerts
|

Genetic thrombophilic mutations among couples with recurrent miscarriage

Abstract: The prevalence of thrombophilic mutations is similar in couples with RM and parous controls. In couples with RM, multiple genetic thrombophilic mutations in either partner significantly increases the risk of miscarriage in a subsequent pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 26 publications
4
38
1
5
Order By: Relevance
“…We used the men as the control group, since thrombophilia is a maternal risk factor that leads to adverse pregnancy outcome. Several studies of couples with spontaneous abortions and fertile couples have found no difference in prevalence of thrombophilic mutations between studied groups ( Jivraj et al, 2006;Jauniaux et al, 2006;Rodger et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
“…We used the men as the control group, since thrombophilia is a maternal risk factor that leads to adverse pregnancy outcome. Several studies of couples with spontaneous abortions and fertile couples have found no difference in prevalence of thrombophilic mutations between studied groups ( Jivraj et al, 2006;Jauniaux et al, 2006;Rodger et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
“…For this reason, many authors have chosen to examine separately the impact of hereditary thrombophilia on each trimester of pregnancy. Controlled studies conducted in the European Caucasian women with a history of unexplained RM failed to demonstrate an association between these two polymorphisms and 1st trimester RM [19,39]. The meta-analyses that have adopted this methodology has also revealed a higher ratio of FLV related losses after the 14th week (OR 2.28) compared with 1st trimester RM (OR 1.6-1.91) [20,26,27,40].…”
Section: In a Controlledmentioning
confidence: 99%
“…Data accumulated over the past two decades have established a clear association between antiphospholipid syndrome (APS), an acquired thrombophilic state, and RM [11][12][13][14][15]. Recent investigations have focused on a higher prevalence of certain inherited thrombophilias, such as factor V Leiden (FVL) and prothrombin (PT) G20210A mutations, in women with unexplained recurrent pregnancy losses [16][17][18][19][20][21]. Nevertheless, these reports have produced conflicting results [22][23][24][25] and this heterogeneity is reflected in existing meta-analyses [17,20,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The study quality may have been affected by differences in the methodological aspects, such as the inclusion of participants with other potential underlying causes of RM or the lack of stratification based on the ethnicity and gestational age of loss of patients (Vettriselvi et al, 2008;Ayadurai et al, 2009). RM is a multifactorial entity; therefore, the variations in the strength of the association between various polymorphisms and RM seen in different studies may be indicative of additional risk factors (Jivraj et al, 2006;Hussein et al, 2010). Therefore, we attempted to diminish these potential biases in this study by selectively including patients with RM that was unexplained during the first trimester.…”
Section: Discussionmentioning
confidence: 99%